Sorafenib in the treatment of hepatocellular carcinoma: a multi-centre real-world study. (2nd August 2016) - Doyle, Adam; Marsh, Philip; Gill, Raghubinder; Rodov, Marcia; Mohsen, Waled; Varma, Poornima; Hong, Thai; Strasser, Simone I.; Bell, Sally; Ryan, Marno; Nicoll, Amanda; Lubel, John; et al.
Abstract: Objective : Sorafenib is an oral multikinase inhibitor that improves survival in advanced hepatocellular carcinoma (HCC). In the absence of alternative therapies, sorafenib is often continued despite advancing liver disease or tumour progression. Real world studies are important to better characterise outcomes in these populations. Our aim was to review patterns of sorafenib use across eight Australian tertiary hospitals, defining variables associated with clinical outcomes.Material and methods : Retrospective cohort study of medical records of 320 patients treated with sorafenib for HCC. Baseline clinical parameters, dosage, adverse effects, and survival from initiation of treatment were collected. Time to radiological progression and 3-month alpha-fetoprotein (AFP) levels were available for a subset of patients.Results : Adverse effects occurred in 79% of patients, requiring dose reduction in 31% of patients. Multivariate analysis identified an increased rate of mortality with Child-Pugh C (HR 5.52, p = 0.012), ECOG performance status 2–3 (HR 2.84, p = 0.001), and extrahepatic metastases (HR 1.54, p = 0.04), and decreased rate of mortality with an AFP reduction of at least 20% at 3 months (HR 0.38, p = 0.001). An increased rate of radiological progression was associated with ECOG performance status 2–3 (HR 2.34, p = 0.041), whilst a decreased rate of radiological progression was associated with development of on-treatment diarrhoea (HR 0.55, p = 0.015).Conclusions : Survival in patients with Child-Pugh C liver function or advanced functional impairment treated with sorafenib is poor and thus routine use of this agent in these patients does not appear justified, particularly given the high rate of adverse effects. AFP concentration on therapy may help identify favourable response to treatment.